An Analysis of Students' Experience in the Use of Moodle in Writing Class during Pandemic Covid-19 - Bobby Iknatius Kurniawan; Ayu Rizki Septiana (Linguists : Journal Of Linguistics and Language Teaching, 2021)
Covid-19 has been declared a worldwide pandemic. The government implemented learning from home to preserve the health of students and school stakeholders. The writing class is frequently conducted through a face-to-face learning scheme. It encouraged learners to interact with their lecturers and receive the materials as well as the feedback directly. Along with the university's online learning policy, Moodle evolved as one of several tools for managing online learning, particularly in writing classes. It constitutes certain limitations on the teaching-learning process.  Students had new experiences as a result of the quick changes in the learning scheme. The researchers aimed to investigate how the students experienced using Moodle in writing class during pandemic COVID 19 and to investigate students’ perception of the effectiveness of using Moodle in writing class. This research is qualitative research. The writer used the phenomenology approach. The participants were 23 students from the fourth semester of the English education department Universitas Bhinneka PGRI.  Interview and questionnaire were used by the researchers in collecting the data. Data analysis can be described in three stages as Organizing and familiarizing and Coding and reducing, and Interpreting and representing. The data was presented in a descriptive form to capture the explanations, thoughts, and experiences of the participants. Based on the students' experiences, the results show that using Moodle in writing class benefited students in a variety of ways, especially during the Covid-19 pandemic. However, there are certain problems that students encountered. Despite their difficulties, they were able to overcome problems. According to the students' perceptions, the use of Moodle in the writing class was generally well-received. According to the majority of students, Moodle is effective in writing class, especially during the Covid-19 pandemic.